Analysis of risk factors for the increased incidence of gallstone caused by hepatectomy: A retrospective case–control study - Zhou, Jiangmin; Chen, Lin; Zhang, Zhiwei; Wu, Biao (Frontiers in Surgery, 2023)
Background An increased risk of gallstones has been observed in patients undergoing hepatectomy. This study attempted to analyze the risk factors for gallstones after hepatectomy. Methods From January 2013 to December 2016, clinical data of 1,452 eligible patients who underwent hepatectomy were consecutively reviewed. According to the imaging, including gallbladder ultrasound, computerized tomography, and magnetic resonance imaging, all patients were divided into the gallstone group and the nongallstone group. Univariate and multivariate logistic regression analyses were performed to select indicators associated with gallstone formation among patients after hepatectomy. Results In the total sample of included patients, there were 341 patients with gallstones and 1,147 patients without gallstones. The incidence of gallstones was 23.5% (341/1,452). The incidence of gallstones in the primary liver cancer group was higher than that in the benign liver tumor group (25.7% vs. 18.9%, P = 0.004). Univariate and multivariate logistic regression analyses showed that female gender, high body mass index, tumor located in S5, and severe postoperative complication were factors related to gallstones in patients with benign liver tumors after hepatectomy. In addition, Child–Pugh B, low albumin, liver cirrhosis, and transcatheter arterial chemoembolization (TACE) after recurrence were factors related to gallstones in patients with primary liver cancer after hepatectomy. Conclusions Hepatectomy increased the risk of gallstones in benign or malignant liver tumors, especially when the tumor was located in S5. TACE further increased the risk of gallstones in patients with postoperative recurrence.